Arguments for a better world : Vol. 2. Societies, institutions, and development : essays in honor of Amartya Sen - Basu, Kaushik; Kanbur, S. M. Ravi.; Sen, Amartya, 1933- (Oxford : Oxford University Press, 2008)
This volume of essays, written in honor of Amartya Sen, covers the range of contributions that Sen has made to knowledge. They are written by some of the world's leading economists philosophers and social scientists, and address topics such as ethics, welfare economics, poverty, gender, human development society, and politics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Welfare economics; Institutional economics; Economics -- Moral and ethical aspects